2022
DOI: 10.3803/enm.2022.101
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Obesity and Metabolic Health on Vascular Health

Abstract: The prevalence of obesity is rapidly increasing worldwide. Obesity should not be understood only as the accumulation of fat in the body, but instead as a phenomenon that exerts different effects on our health according to the place of fat deposition and its stability. Obesity is the starting point of most metabolic diseases, such as diabetes, hypertension, metabolic syndrome, sleep apnea, and eventually cardiovascular disease. There are different kinds of obesity, ranging from simple obesity to sarcopenic obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Similar findings were observed in a 24-year follow-up cohort, which showed that sarcopenic obesity is clinically useful as a predictor of all-cause mortality [ 33 ]. Sarcopenic obesity is also related to cognitive impairment [ 29 ], low bone mineral density [ 26 ], frailty [ 7 ], and metabolic diseases [ 34 ]. A study found that carbohydrate intake could be the best indicator for determining sarcopenic obesity in older adults [ 35 ], and body composition plays an important role in sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were observed in a 24-year follow-up cohort, which showed that sarcopenic obesity is clinically useful as a predictor of all-cause mortality [ 33 ]. Sarcopenic obesity is also related to cognitive impairment [ 29 ], low bone mineral density [ 26 ], frailty [ 7 ], and metabolic diseases [ 34 ]. A study found that carbohydrate intake could be the best indicator for determining sarcopenic obesity in older adults [ 35 ], and body composition plays an important role in sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal obesity is a well-known risk factor for metabolic disease [ 24 ]. Strategies that aid the sustained reduction and maintenance of abdominal obesity assessed by WC can prevent or delay the progression of MetS and associated chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by an accumulation of fat in the liver that is not related to alcohol consumption [ 1 ] but that is related to overweight and obesity [ 2 , 3 ], insulin resistance [ 4 ], states of hyperglycemia [ 3 , 5 ], and high levels of triglycerides in the blood. As such, it is also related to metabolic dysfunction [ 4 , 6 , 7 , 8 ] and increased cardiovascular risk factors [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%